2007
DOI: 10.1039/b613434c
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical analysis of a classic example of supramolecular catalysis

Abstract: Computational chemistry is used to study a 1,3-dipolar cycloaddition between an azide and an alkyne inside the macrocycle cucurbit[6]uril, in order to elucidate the catalytic function of a highly efficient supramolecular catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 19 publications
(35 reference statements)
6
54
1
Order By: Relevance
“…1). Further, our calculated geometric parameters are consistent with the previously reported values using B3LYP functionals [16,20]. Our calculated energy gap of 6.58 eV (HOMO-LUMO) for CB- [6] is close to the values reported in earlier calculations [16].…”
Section: Resultssupporting
confidence: 93%
“…1). Further, our calculated geometric parameters are consistent with the previously reported values using B3LYP functionals [16,20]. Our calculated energy gap of 6.58 eV (HOMO-LUMO) for CB- [6] is close to the values reported in earlier calculations [16].…”
Section: Resultssupporting
confidence: 93%
“…Very recently, computational chemistry has been used to investigate the supramolecular catalytic cycloaddition [22]. An argument based on the calculated results showed that the slow reaction of the non-catalytic 1,3-dipole cycloaddition was caused by thermodynamic barriers (calc.…”
Section: Cucurbit[6]uril-induced Chemical Controlmentioning
confidence: 99%
“…The encapsulation, moreover, had no noticeable effect on the photochemical degradation of ranitidine dihydrochlride, the effective form for treatment of the disease, at pH 1.5; therefore it cannot prevent degradation of the drug excreted from human body. Lansoprazole (22 ) and Omeprazole (23), which are used to treat the classic disease of excessive secretion of gastric acid, have enhanced solubility in aqueous solutions and the acidic stability has been improved by 4 pH units via encapsulation within Q [7], allowing increased application of the drugs in a more extensive pH range [41]. The encapsulation of drug guests within Q[7] eliminated or decreased unwanted side effects, while the activation was preserved or allayed slightly with enhanced stability.…”
Section: Cucurbit[7]uril-induced Chemical Controlmentioning
confidence: 99%
“…By bringing in close contact reactive groups of one or more molecules, they may enhance the rate of a specific chemical reaction. [7][8][9] Sanders used a porphyrin trimer to catalyze a Diels-Alder reaction with up to a 1030-fold acceleration. A series of successful examples have been reported in the past several decades.…”
Section: Introductionmentioning
confidence: 99%